Sustainable Synthesis of Dual Single‐Atom Catalyst of PdN4/CuN4 for Partial Oxidation of Ethylene Glycol - Moges, Endalkachew Asefa; Chang, Chia‐Yu; Huang, Wei‐Hsiang; Lakshmanan, Keseven; Awoke, Yohannes Ayele; Pao, Chih‐Wen; Tsai, Meng‐Che; Su, Wei‐Nien; Hwang, Bing Joe (Advanced functional materials, 2022)
Catalysts assumed that properly designed bimetallic systems would provide superior catalytic performance due to the cooperative effects between two atoms. Dual single‐atom catalyst (DSAC) PdN4/CuN4 is synthesized using a simple, cost‐effective, and efficient electrochemical reduction method. The palladium single‐atom is prepared first by electrochemical reduction of copper phthalocyanine to create defective N4 sites. The new structural feature is characterized by copper reduction from Cu‐N4 coordination and the formation of defected N4 (▫M‐N4) sites, which react with a Pd precursor and form PdN4 on the host surface. The DSAC PdN4/CuN4 technique synergistically improves electrocatalytic performance toward the ethylene glycol oxidation reaction. It possesses excellent glycolate selectivity (above 88%) in an alkaline solution with an onset oxidation potential as low as 0.6 V versus a reversible hydrogen electrode, compared to commercial Pd/C. The DSAC electrocatalyst is characterized by its high current density of 83.92 mA cm−2 and high faradic efficiency value (>80%) for glycolate at 1.0 VRHE. The findings suggest a promising method to synthesize the DSACs in varying transition metals to achieve highly efficient, selective, and environmentally friendly catalysts for different applications. Dual single‐atom catalyst (DSAC) PdN4/CuN4 is synthesized by a cost‐effective and efficient electrochemical reduction method. Using an inexpensive copper phthalocyanine molecular complex as the starting material, Pd is integrated into N4 defective sites of the macrocyclic phthalocyanine (Pc2‐). The DSAC provides insights into the catalytic and structural active sites of ethylene glycol oxidation.